Surgical treatment of neovascular glaucoma with Ex-PRESS glaucoma shunt: Case report. Issue 35 (September 2017) - Yu, Teng-Chieh; Tseng, Gow-Lieng; Chen, Chun-Chen; Liou, Shiow-Wen
Abstract: Rationale: Neovascular glaucoma (NVG) is one of the most aggressive types of glaucoma, and its abnormal fibrovascular tissue growth on the iris and trabecular meshwork may create difficulties to control the intraocular pressure (IOP) and perform the operation such as trabeculectomy. Patient concerns: Ex-PRESS glaucoma shunt has been introduced to serve as one alternative operation for glaucoma, and is thought to have the potential advantage of being less traumatic than traditional trabeculectomy. The purpose of our study is to evaluate the efficacy and safety of primary Ex-PRESS implantation in eyes with NVG. Diagnoses and interventions: This was a retrospective study of four patients with NVG in whom primary Ex-PRESS implantation was performed between January 2012 and October 2016. Outcomes: After a mean follow-up of 20.8 ± 8.9 months (range, 15–34 months), three of four NVG patients (75.0%) receiving primary Ex-PRESS implantation had postoperative IOP under 21 mmHg without any antiglaucoma medication control at the last follow-up, but shunt reposition had been performed due to failed blebs or recurrent NVG. Besides, the best corrected visual acuity at the last follow-up was stabilized or improved in three of four NVG patients (75.0%), accompanied with the regression of iris neovascularization. Only one patient had self-resolved postoperative hyphema; otherwise, there were no other perioperative complications. Lessons: Primary Ex-PRESS implantation might constitute a safe and alternative treatment for patients with NVG. In spite of the possible reoperations, the final outcomes were still shown effective after shunt reposition.